THE NEXUS BETWEEN WOMEN'S HUMAN DEVELOPMEN INDEX AND WOMEN’S INCOME DISTRIBUTION - Diah Lufti Wijayanti; Suprapti, Sri Budiwati Wahyu; Rahayu, Astuti; Nurlitasari, Arini (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This research aims to investigate the relationship between women's income contributions and the Human Development Index (HDI) for women in Central Java Province over the period from 2014 to 2023. The analysis is based on secondary data provided by the BPS. The study employs a causality test to determine the direction and strength of the relationship between the two variables. The findings reveal that the HDI for women plays a significant role in influencing women's income contributions. Specifically, the HDI, which encompasses indicators such as education, health, and living standards, proves to be a key determinant of the variations in women's economic contributions within the province. This conclusion is supported by the R-squared value of 0.6238, indicating that 62.38% of the changes in women's income contributions can be explained by fluctuations in their HDI. These results highlight the crucial link between human development and women's economic participation, suggesting that policies aimed at improving women’s HDI could lead to greater economic contributions from women in the region. Ultimately, the study provides valuable insights into how enhancing women's overall well-being positively impacts their role in regional economic development.